Are megaprojects ready for the Fourth Industrial Revolution?. Issue 2 (23rd June 2020) - Whitmore, David; Papadonikolaki, Eleni; Krystallis, Ilias; Locatelli, Giorgio
Abstract : Complex projects and megaprojects are increasingly shaped by new enabling technologies and new demands from businesses, including how people are treated when working on these endeavours. This is often referred to as the Fourth Industrial Revolution (4IR). Project leaders and practitioners are not fully leveraging the opportunities unlocked by the 4IR, and project performance shows little sign of improvement despite the highly innovative and collaborative environment that the 4IR stimulates. This paper discusses this challenge and concludes that a significant reason why these benefits are not being realised is because there is a competence gap in both the project leader and practitioner communities. These communities are attempting to deal with twenty-first-century issues using competences, toolsets and a mindset created 100 years ago. Significant developments in competences associated with the 4IR in general are required. In this paper, specific competences are proposed and justified: collaborative working including people, process and digital components; lean six sigma; and agile. Success will be to empower the people who deliver megaprojects such that they are able to deliver the planned social value to all stakeholders involved.